Altered sleep composition after traumatic brain injury does not affect declarative sleep-dependent memory consolidation - Mantua, Janna; Mahan, Keenan M.; Henry, Owen S.; Spencer, Rebecca M. C. (Frontiers in Human Neuroscience, 2015)
Individuals with a history of traumatic brain injury (TBI) often report sleep disturbances, which may be caused by changes in sleep architecture or reduced sleep quality (greater time awake after sleep onset, poorer sleep efficiency, and sleep stage proportion alterations). Sleep is beneficial for memory formation, and herein we examine whether altered sleep physiology following TBI has deleterious effects on sleep-dependent declarative memory consolidation. Participants learned a list of word pairs in the morning or evening, and recall was assessed 12-hrs later, following an interval awake or with overnight sleep. Young adult participants (18-22 yrs) were assigned to one of four experimental groups: TBI Sleep (n=14), TBI Wake (n=12), non-TBI Sleep (n=15), non-TBI Wake (n=15). Each TBI participant was >1 yr post-injury. Sleep physiology was measured with polysomnography. Memory consolidation was assessed by comparing change in word-pair recall over 12-hr intersession intervals. The TBI group spent a significantly greater proportion of the night in SWS than the non-TBI group at the expense of NREM1. The TBI group also had marginally lower EEG delta power during SWS in the central region. Intersession changes in recall were greater for intervals with sleep than without sleep in both groups. However, despite abnormal sleep stage proportions for individuals with a TBI history, there was no difference in the intersession change in recall following sleep for the TBI and non-TBI groups. In both Sleep groups combined, there was a positive correlation between Intersession Change and the proportion of the night in NREM2 + SWS. Overall, sleep composition is altered following TBI but such deficits do not yield insufficiencies in sleep-dependent memory consolidation.